Excessive Exercise—A Meta-Review - Colledge, Flora; Cody, Robyn; Buchner, Ursula G.; Schmidt, André; Pühse, Uwe; Gerber, Markus; Wiesbeck, Gerhard; Lang, Undine E.; Walter, Marc (Frontiers in Psychiatry, 2020)
Background and aims While a number of studies have reported on individuals who exercise excessively, and feel unable to stop despite negative consequences, there is still insufficient evidence to categorize exercise as an addictive disorder. The aim of this meta-review is to summarize the published articles and to compile a list of symptoms reported in the qualitative literature in conjunction with excessive exercise. This list is compared with the DSM-5 criteria for gambling disorder, and initial diagnostic criteria for exercise addiction are suggested. Methods The databases MEDLINE, Web of Science and PsycInfo were searched for qualitative studies or case reports, in which excessive exercise was the main focus. All symptoms reported in conjunction with excessive exercise were extracted from each study and documented. Symptoms were also compared to the diagnostic criteria for gambling disorder. Results 17 studies were included in the review, yielding 56 distinct symptoms. The Critical Appraisal Skills Program tool showed that the majority of the studies were of acceptable quality. Exercise-related symptoms corresponded with 7 of the 9 DSM-5 criteria for gambling disorder. The 10 suggested criteria for exercise addiction are: increasing volume, negative affect, inability to reduce, preoccupation, exercise as coping, continuation despite illness/injury, minimization, jeopardized relationships, continuation despite recognizing consequences, guilt when exercise is missed. Discussion Our results suggest that excessive exercise may constitute a behavioral addiction, based on the criteria of the DSM-5. Conclusions Subsequent studies should aim to systematically classify symptoms of excessive exercise; in addition, it should be noted that basic questionnaires may be need to be supplemented with detailed clinical and neurobiological examinations.